2021
DOI: 10.1111/bph.15464
|View full text |Cite
|
Sign up to set email alerts
|

Differential mode of cholesterol inclusion with 2‐hydroxypropyl‐cyclodextrins increases safety margin in treatment of Niemann‐Pick disease type C

Abstract: Background and Purpose Niemann‐Pick disease type C (NPC) is a lysosomal storage disorder with disrupted intracellular cholesterol trafficking. A cyclic heptasaccharide, 2‐hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD), is a cholesterol solubilizer that is being developed to treat NPC, but its ototoxicity and pulmonary toxicity remain important issues. We have characterized 2‐hydroxypropyl‐γ‐cyclodextrin (HP‐γ‐CD), a cyclic octasaccharide with a larger cavity than HP‐β‐CD, as a candidate drug to treat NPC. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 55 publications
(99 reference statements)
1
10
0
Order By: Relevance
“…[11][12][13][14][15][16][17] We previously identified that 2-hydroxypropyl-γ-CD (HP-γ-CD), a γ-CD derivative with a larger cavity diameter than HP-β-CD, fine-tunes UC solubilization by forming a distinct UC inclusion mode from HP-β-CD and restores cholesterol balance in cells and murine models of NPC more safely than HP-β-CD. [18][19][20] We further reported the safety advantages and favourable physicochemical properties of chemically pure, mono-branched CD derivatives with α-1,6-linked maltosyl derivatives over HP-β-CD in NPC experimental models. [21][22][23] In another approach, we synthesized several drug delivery system-based derivatives targeting affected organs to improve the bioavailability of highly excretable CDs.…”
Section: Introductionmentioning
confidence: 94%
“…[11][12][13][14][15][16][17] We previously identified that 2-hydroxypropyl-γ-CD (HP-γ-CD), a γ-CD derivative with a larger cavity diameter than HP-β-CD, fine-tunes UC solubilization by forming a distinct UC inclusion mode from HP-β-CD and restores cholesterol balance in cells and murine models of NPC more safely than HP-β-CD. [18][19][20] We further reported the safety advantages and favourable physicochemical properties of chemically pure, mono-branched CD derivatives with α-1,6-linked maltosyl derivatives over HP-β-CD in NPC experimental models. [21][22][23] In another approach, we synthesized several drug delivery system-based derivatives targeting affected organs to improve the bioavailability of highly excretable CDs.…”
Section: Introductionmentioning
confidence: 94%
“… 39 , 40 ) At present, a variety of agents are being investigated for improved efficacy in the treatment of NPC. 41 , 42 )…”
Section: Introductionmentioning
confidence: 99%
“…A critical property of β-CDs in pharmaceutical and biomedical applications is the formation of inclusion complexes with a variety of guest molecules, including small molecular drugs and cholesterol. , The pharmacological applications of β-CDs have recently gained increasing attention due to their potential therapeutic effect on various metabolic diseases such as Niemann-pick type C disease, Alzheimer’s disease, atherosclerosis, and diabetic kidney disease . β-CDs are believed to interact with intracellular cholesterol and improve cholesterol metabolic abnormalities, resulting in the proclaimed therapeutic effects. Due to high water solubility, low toxicity, and excellent cholesterol inclusion ability, 2-hydroxypropyl β-CD (HP-β-CD) has been widely utilized in these studies , However, the effective dose of HP-β-CD for the treatment of metabolic diseases is typically quite high (ca. 4000 mg/kg), owing to its rapid renal clearance and low tissue accumulation. , Such a high dosage of HP-β-CD has been reported to cause tissue injury and ototoxicity. …”
Section: Introductionmentioning
confidence: 99%